Neural signatures of perceptual closure and top-down feedback in lexical access: an ERP study. - Civera, Teresa; Perea, Manuel; Comesaña, Montserrat; Gutierrez-Sigut, Eva; Vergara-Martínez, Marta (Language, Cognition & Neuroscience, 2026)
Perceptual Closure, the ability to recognise incomplete stimuli by integrating prior knowledge, has been well-studied in object perception but remains largely unexplored in language research. We examined how lexical feedback (word frequency) interacts with bottom-up visual processing when word stimuli are incomplete. Using event-related potentials (ERPs), participants performed a lexical decision task with high – and low-frequency words in complete or incomplete (top-only) formats. Behavioural results showed additive effects of word frequency and completeness. ERP analyses revealed that completeness affected early perceptual components (P100, N170) and closure-related responses (VAN, P300), while word frequency modulated later lexical-semantic processing (N400). Crucially, word frequency effects emerged earlier for incomplete (350–450 ms) than complete words (450–600 ms), suggesting lexical feedback helps disambiguate perceptually difficult stimuli. Overall, these findings provide insights into the interplay between visual and linguistic information, linking models of word recognition and reading with broader cognitive and neural mechanisms of perception.